Multiple Segments Thoracal Spinal Canal Stenosis Caused by Ossification of Ligamentum Flavum: A Case Report - Wiguna, I Gusti Lanang Ngurah Artha; Raditya, I Nyoman Yuda; Arimbawa, Ida Bagus Gede (Indonesian Journal of Medicine, 2022)
Background: Thoracal spinal canal stenosis (SCS) that refers to multiple segments of the thoracic spine is a peculiar clinical condition. Various factors can cause thoracic SCS, including ossification of the ligamentum flavum (OLF). The aim of this study is to explain about the diagnosis for multiple segment thoracal spinal canal stenosis and management properly to prevent further complications.Case Presentation: A 58-year-old male came to Orthopaedic Outpatient Clinic in Prof. I.G.N.G Ngoerah Hospital, complaining back pain since one year prior to admission. Pain aggravated when he was bending his back. The patient was diagnosed with Thoracal Spinal Canal Stenosis Th 8-9, Th9-10, Th10-11. Patient underwent decompression, stabilization, fusion and biopsy surgery.Results: Patient underwent decompression, stabilization, fusion and biopsy surgery at RSUP Prof. I.G.N.G Ngoerah. In durante operation, already done laminectomy and eight pieces of pedicle screw was applied in Th8-Th11 (55mm x 40 mm Monoaxial on right side Th8, 55mm x 40 mm Polyaxial on left side Th8; 55mm x 40 mm Monoaxial on right side Th9, 55mm x 35 mm Monoaxial on left side Th9; 55mm x 40 mm Monoaxial on right and left side Th10; 55mm x 40 mm Monoaxial on right and left side Th11). There were no complications found in this patient after 4th day following surgery.Conclusion: The goal of surgical intervention for SCS is decompression by removing the calciﬁc areas that are responsible for the spinal canal narrowing and subsequent cord compression. Although the diagnosis and choice of intervention can be difﬁcult, early detection and management are critical to postoperative success. Postoperative results are variable and often unsatisfactory.Keywords: Spinal canal stenosis, ligamentum flavum, spine, surgeryCorrespondence: I Gusti Lanang Ngurah Artha Wiguna. Division of Spine, Department of Orthopaedic and Traumatology, Prof. I.G.N.G Ngoerah Hospital, Faculty of Medicine, Udayana University, Bali, Indonesia. Email:lanangwiguna20021979@gmail.com. Mobile: 0811388859.Indonesian Journal of Medicine (2022), 07(03): 278-288https://doi.org/10.26911/theijmed.2022.07.03.04